Centroid Jamming Strategy for Reconnaissance and Strike Integrated UAV Based on Chaff Cartridge Protection - Qing Chaojin, He Linsi, Wei Maogang, Wang Zilong (Hangkong bingqi, 2024)
To address the issue of weak anti-strike capability and poor survival capability for medium and large-sized reconnaissance and strike integrated unmanned aerial vehicles (RSUAVs) in medium-altitude environments, this paper investigates a centroid jamming strategy for RSUAVs protected by chaff cartridges. The strategy uses the closest distance between the missile and the RSUAV as an evaluation index, aiming to extend the survival time of RSUAVs under missile threats and thus to improve the survival probability of RSUAVs during mission execution. Firstly, detailed motion models of RSUAV, chaff cloud, and missile are constructed, the forming processing of chaff cloud is deeply analyzed, and the velocity difference between the chaff cartridge deployment and actual launch is explored in detail. Considering the centroid motion model of multiple chaff clouds coexisting simultaneously, combining relevant parameters of chaff cartridge deployment, centroid jamming constraint conditions and interval times are formed. Finally, at the end of the centroid jamming, the RSUAV escape indicator is used to determine whether the RSUAV has successfully escaped. The simulation results demonstrate that under the given initial distance and escape time conditions, the closest distance between the missile and the RSUAV increases to more than 127 times of the missile explosion range, and prolongs the survival time of the RSUAV by about 62.5%. The proposed method can help to improve the survival probability of RSUAV, and it presents the effectiveness and robustness with the parameters variations of missile, chaff cartridge, and environmental conditions.